RHETORIC VERSUS REALITY IN SOUTH AFRICA'S POLICY DISCOURSE ON HIGHER EDUCATION INSTITUTIONS: A CRITICAL REVIEW - Shaikh, Ahmed; Blom, Ronel; Soni, Dhiru; Botha, Christoff; Bisschoff, Christo (Journal of Economic Development, Environment and People, 2024)
The South African Department of Higher Education and Training issued a Draft Policy for discussing the reclassification of tertiary education institutions. This article scrutinised the proposed policy and provided feedback to the department regarding the challenges, potential considerations, and imperatives of reclassifying higher education institutions in the educational landscape. The study employs a quantitative focus-group research design whereby six experts in Education discussed the impact of policy changes across several educational realities. The role of universities (and other higher education institutions) is discussed, and the results show that the Draft Policy lacks synergy with the country's National Development Plan 2023. There is also a lack of dialogue between public and private higher education institutions, while the Draft Policy neglects Public Private Partnerships. The study recommends that the Minister of Education establish a Research and Development Committee constituted of Public and Private higher education institutions to collaboratively advise and guide the process of reclassifying higher education institutions in South Africa. This committee will also assist the Minister in reimagining what a future South African university should look like in the current turbulent educational environment where demographic shifts, geopolitical challenges, changing workplace demands and high student expectations for a quality digital experience exist.